Scientists' Warning on the Conservation of Subterranean Ecosystems. (19th June 2019) - Mammola, Stefano; Cardoso, Pedro; Culver, David C; Deharveng, Louis; Ferreira, Rodrigo L; Fišer, Cene; Galassi, Diana M P; Griebler, Christian; Halse, Stuart; Humphreys, William F; Isaia, Marco; Malard, Florian; et al.
Abstract: In light of recent alarming trends in human population growth, climate change, and other environmental modifications, a "Warning to humanity" manifesto was published in BioScience in 2017. This call reiterated most of the ideas originally expressed by the Union of Concerned Scientists in 1992, including the fear that we are "pushing Earth's ecosystems beyond their capacities to support the web of life." As subterranean biologists, we take this opportunity to emphasize the global importance and the conservation challenges associated with subterranean ecosystems. They likely represent the most widespread nonmarine environments on Earth, but specialized subterranean organisms remain among the least documented and studied. Largely overlooked in conservation policies, subterranean habitats play a critical role in the function of the web of life and provide important ecosystem services. We highlight the main threats to subterranean ecosystems and propose a set of effective actions to protect this globally important natural heritage.